INVESTIGATING ANTIMICROBIAL RESISTANCE PRACTICES IN PAKISTAN’S LIVESTOCK SECTOR: IMPLICATIONS FOR HUMAN AND ANIMAL HEALTH POLICY (The Research of Medical Science Review, 2025)
Antimicrobial resistance (AMR) poses an increasing threat to global public health, particularly in low- and middle-income nations where regulatory control over antibiotic utilization is inadequate. The unregulated and excessive use of antimicrobials in Pakistan's poultry and dairy cattle sectors has led to the development of drug-resistant bacterial strains, posing a threat to both animal and human health. This study examined the incidence of antimicrobial resistance (AMR) and its behavioral determinants in a veterinary context, utilizing a One Health approach to evaluate hazards at the animal-human interface. This study aimed to assess antimicrobial resistance patterns in significant pathogens and investigate the knowledge, attitudes, and practices regarding antibiotic use among stakeholders in Pakistan's poultry and dairy cow industries. A cross-sectional, mixed-methods study was conducted at University of Veterinary and Animal Sciences, Lahore, Punjab, Pakistan. Data was gathered from 300 livestock stakeholders via structured surveys, and 100 biological samples were examined for resistant strains of Escherichia coli, Salmonella spp., and Staphylococcus aureus using the Kirby-Bauer disk diffusion method. Statistical methods, including chi-square tests and regression models, were employed to assess the relationship between antibiotic use and the development of resistance. The findings indicated significant resistance levels among all three infections, with S. aureus in dairy cattle exhibiting the highest resistance at 88% and E. coli in poultry also displaying considerable rates at 87%. Survey findings revealed that 68% of respondents used antibiotics without veterinary prescriptions, and more than half were unaware of antimicrobial resistance (AMR). A substantial correlation was identified between inadequate awareness and antibiotic abuse (P < 0.05). These findings underscore the pressing need for targeted awareness initiatives, veterinary management programs, and policy measures to mitigate the irrational use of antibiotics. This study offers essential evidence to endorse integrated antimicrobial resistance control strategies in Pakistan's animal health systems.